Development of Plasmonic Nanosandwiches for Biosensing Applications - Moura, André de Távora Vasconcelos de (2019)
Structures composed of two gold disks with different diameters and separated by a thin alumina layer were studied for protein biodetection. The small top disk will be used as the biosensing element since it has a shorter decay length (and thus, it has a higher sensitivity) whereas the big bottom one will give a high signal due to its bigger interaction with light. The interaction between both disks will happen through plasmon hybridisation. The samples were prepared using colloidal lithography and material deposition was made through an electron beam assisted evaporation system. A fabrication method was developed to spatially isolate the bottom disk from the sensing medium to fully exploit the small disk’s higher sensitivity. Sample’s characterisation consisted in a morphologic analysis by scanning electronic microscopy (SEM), the optical response was studied experimentally and by finite-domain time-difference (FDTD) simulations and also the electric field distribution was analysed in three types of structures. Structures with the upper disk centred relative to the lower disk and at the edge of it. The oxide’s thickness effect was studied (3 and 6 nm). The low energy peak is mainly given by a plasmonic gap dipole mode, whereas as the high energy peak is given by a contribution from a gap mode and the structure’s overall net dipole. The structure with a smaller separation and the top disk centre regarding the bottom disk was found to have a higher electric field enhancement around it and should be the one to be used as a biosensor.